2001
DOI: 10.1053/seiz.2000.0504
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam does not modulate neuronal voltage-gated Na+and T-type Ca2+currents

Abstract: This study investigated whether the mechanism of action of levetiracetam (LEV) is related to effects on neuronal voltage-gated Na+ or T-type Ca2+currents. Rat neocortical neurones in culture were subjected to the whole-cell mode of voltage clamping under experimental conditions designed to study voltage-gated Na+ current. Additionally, visually identified pyramidal neurones in the CA1 area of rat hippocampal slices were subjected to the whole-cell mode of voltage clamping under experimental conditions designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 23 publications
(31 reference statements)
8
83
2
3
Order By: Relevance
“…This appears to exclude that a direct facilitation by LEV of GABAergic inhibition is involved in its anti-epileptic activity in humans. Together with reports showing an absence of eect on both voltage-operated Na + and T-type Ca 2+ currents (Zona et al, 2001), this suggests that LEV does not induce a conventional modulation of any of the three main mechanisms involved in the anti-epileptic action of classical AEDs. Instead, the present study revealed that LEV was the only AED showing a consistent suppression of the inhibition by both bcarbolines and zinc on GABA-and glycine-gated currents.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This appears to exclude that a direct facilitation by LEV of GABAergic inhibition is involved in its anti-epileptic activity in humans. Together with reports showing an absence of eect on both voltage-operated Na + and T-type Ca 2+ currents (Zona et al, 2001), this suggests that LEV does not induce a conventional modulation of any of the three main mechanisms involved in the anti-epileptic action of classical AEDs. Instead, the present study revealed that LEV was the only AED showing a consistent suppression of the inhibition by both bcarbolines and zinc on GABA-and glycine-gated currents.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies have shown that LEV is devoid of impact on the voltage-activated tetrodotoxin-sensitive inward Na + current in cultured rat cortical neurons and on the low-voltage-activated (T-type) Ca 2+ current in pyramidal neurons from rat hippocampal slices (Zona et al, 2001). This suggests that inhibition of voltage-operated Na + or T-type Ca 2+ channels is not involved in the anti-epileptic mechanism of LEV.…”
Section: Introductionmentioning
confidence: 99%
“…7 LEV seems to partially inhibit N-type high voltage-activated Ca 2+ currents and reduces Ca 2+ release from intraneuronal stores; it reverses the effects of negative allosteric modulators of gamma aminobutyric acid and glycine-gated currents. [8][9][10] Recently, the LEV binding site was identified as synaptic vesicle protein 2A (SV2A). 11 A very recent study 12 has explored the hypothesis that the antiepileptic mechanism of action of LEV is related to effects on alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptor channels in mouse cortical neurons.…”
mentioning
confidence: 99%
“…Action mechanism of levetiracetam has not been understood clearly yet (37). It is thought in some studies related to the action mechanism of levetiracetam that it regulates highvoltage N-type calcium channels and potassium flow (22).…”
Section: Resultsmentioning
confidence: 99%